Caractérisation physico-chimique d’un système lotique en région tropicale : la rivière Sô au Sud-Bénin, Afrique de l’Ouest - KOUDENOUKPO, Zinsou Cosme; CHIKOU, ANTOINE (My University, 2017)
Objective: To carry out a physicochemical characterization of the waters of the Sô River in order to provide basic elements for future ecological modeling of the system. Methodology and Results: Data were collected monthly between June 2015 to November 2016 at twelve sampling stations. Sixteen physico-chemical parameters, eight in situ (temperature, pH, transparency, depth, salinity, dissolved oxygen, electrical conductivity and Dissolved Total Solids) and eight physico-chemical parameters (NTK, NO2-, NO3-, NH4+ , PO43- PO43-total, Ca2+ and Mg2 +) were measured. The Kruskal Wallis and SNK test, correlation matrix, Ascending Hierarchy Classification (HCA) and Principal Component Analysis (PCA) were applied to all measured parameters. The results identified four groups of stations with 80% dissimilarity. Group 1, consisting of the stations of the lower course, contains highly mineralized waters, groups 2 and 3 consisting of the stations of the middle course, show a nitrogenous and phosphorous pollution and the group 4 consisting of the stations of the upper course of the river presents the characteristics of very well oxygenated waters and favorable to the growth of aquaculture species. Conclusions and applications : the upstream part of the Sô River has waters for good fish productivity while the downstream and middle courses present waters with high levels of nitrogen and phosphorus compounds disrupting the biotope, which could create an imbalance in fauna aquatic. These results provide basic data for the implementation of a sustainable management plan for the river and its watershed.
Keywords: Physico-chemistry; Pollution; Lotic system; Sô River; Tropical region